Martian Oxygen and Hydrogen Upper Atmospheres Responding to Solar and Dust Storm Drivers: Hisaki Space Telescope Observations. Issue 12 (23rd December 2020) - Masunaga, K.; Yoshioka, K.; Chaffin, M. S.; Deighan, J.; Jain, S. K.; Schneider, N. M.; Kimura, T.; Tsuchiya, F.; Murakami, G.; Yamazaki, A.; Terada, N.; Yoshikawa, I.
Abstract: We present variations of oxygen 130.4 nm and hydrogen Ly‐β airglow of the Martian upper atmosphere observed by the Hisaki spacecraft in the Earth orbit. In 5‐year intermittent observations covering various Mars seasons, the 130.4 nm brightness varied from ∼700 to ∼1, 200 Rayleigh, correlated with the solar 130.4 nm flux. The Ly‐β brightness, on the other hand, varied from ∼50 to ∼260 Rayleigh, correlated with the column dust optical depth rather than the solar Ly‐β flux. This suggests that the global oxygen column density in the upper atmosphere was relatively stable over the observations while the hydrogen column density was highly variable, controlled by dust storms. Although the observations were made in different Mars Years, we suggest that the hydrogen column density increased by at least 2–5 times from non‐dusty to dusty seasons. The source of the hydrogen atoms is likely water vapor transported from the lower atmosphere which subsequently photodissociate into hydrogen atoms. The amount of oxygen atoms dissociated from water vapor is small compared with those dissociated from the main CO2 atmosphere. Large brightness of both emissions was detected during the comet siding spring (CSS) approach. We suggest that a large solar 130.4 nm flux caused the large 130.4 nm brightness and an effect of the CSS approach was small. For Ly‐β, a regional dust storm during the CSS approach likely caused the large brightness. Although it is possible that the hydrogen atoms are transported from the comet, we leave the effect of CSS on the Ly‐β brightness uncertain. Plain Language Summary: The amount of oxygen and hydrogen in the Martian upper atmosphere is a topic of interest for decades to understand water loss from Mars. Recent observations suggest that the Martian upper atmosphere is not only affected by external solar drivers but also dust activities in the lower atmosphere of Mars. On Mars, dust lifted from the surface is a major atmospheric heat source and known to affect the atmospheric circulation pattern. The Hisaki spacecraft is a space telescope orbiting the Earth and has intermittently observed Martian extreme ultraviolet airglow since its launch in 2013. Since the Earth‐based remote observation captures a whole disk of Mars, it is an useful tool to study global abundance of the Martian upper atmospheric components. Analyzing oxygen 130.4 nm and hydrogen Ly‐β airglow emissions, we found that the disk brightness of oxygen 130.4 nm strongly correlated with the solar 130.4 nm flux while Ly‐β disk brightness correlated with dust storm activities in the lower atmosphere. This suggests that oxygen abundance in the upper atmosphere was relatively stable while hydrogen abundance was controlled by dust storms that transport water vapor dissociating into hydrogen atoms from the lower to upper atmospheres of Mars. Key Points: Seasonal variations of OI 130.4 nm and HI Ly‐β airglow emissions of Mars were observed by an Earth‐based space telescope 130.4 nm airglow varied with the solar 130.4 nm flux and oxygen abundance was likely stable even during dust storms and the comet approach Ly‐β airglow varied with dust storms and hydrogen abundance increased by at least ∼2–5 times from nondusty to dusty seasons